2003
DOI: 10.1007/s00223-001-2088-5
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF) Induces the Osteoblastic Differentiation of the Human Osteosarcoma Cell Line SaOS-2

Abstract: The Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF) is a hematopoietic growth factor that regulates the in vitro and in vivo proliferation and differentiation of hematopoietic cells through the interaction with a specific heterodimeric receptor complex (GM-CSFR), consisting of an alpha and a beta chain with molecular weights of 80 and 120 KDa, respectively. We have studied the expression of the GM-CSFR (alpha chain) on the surface of the human osteosarcoma cell line SaOS-2 and the in vitro effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 39 publications
4
40
1
Order By: Relevance
“…First, OS cells exhibit the characteristics of undifferentiated osteoblasts. 3,[33][34][35][36][37][38][39] Second, we demonstrated that differentiationpromoting agents (eg, PPARg agonists and 9-cis retinoic acid) can induce OS differentiation and inhibit OS proliferation. 3,40 Third, a recent study that showed Runx2 and p27 KIP1 -mediated osteoblast terminal differentiation is disrupted in OS.…”
Section: Osteogenic Bmps Promote Cell Proliferation In Early Progenitmentioning
confidence: 81%
“…First, OS cells exhibit the characteristics of undifferentiated osteoblasts. 3,[33][34][35][36][37][38][39] Second, we demonstrated that differentiationpromoting agents (eg, PPARg agonists and 9-cis retinoic acid) can induce OS differentiation and inhibit OS proliferation. 3,40 Third, a recent study that showed Runx2 and p27 KIP1 -mediated osteoblast terminal differentiation is disrupted in OS.…”
Section: Osteogenic Bmps Promote Cell Proliferation In Early Progenitmentioning
confidence: 81%
“…SaOS-2 cells represent a good in vitro model to study the interaction of cells with implant biomaterials exhibiting large analogies with immature osteoblast cells [38][39][40][41]47) compared to other immortalized cell lines. Shapira and Halabi 43) recently reported that, in contrast to primary cultured human osteoblasts that do not yield consistent results due to their tendency to lose the osteoblastic phenotype during cell culture, SaOS-2 cells showed more manageability without loss of phenotypical expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several primary and transformed cell lines have been used to develop culture systems to study the interaction of cells with implant biomaterials 8,14,[17][18][19][36][37][38][39][40][41][42][43][44][45][46] . SaOS-2 is an osteoblast-like cell line, derived from a human osteosarcoma, that several studies have demonstrated to be a relevant cell model, due to its large analogies with immature osteoblast cells [38][39][40][41]47) and better manageability when compared to primary human cell Sandblasted-acid-etched titanium surface influences in vitro the biological behavior of SaOS-2 human osteoblast-like cells culture 43) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shiigai et al 30) reported that an extracellular matrix (ECM), which is more than 100 nm wide and contains fibronectin and integrin, might be created between the wall of an MF and an L-929 fibroblast. Several studies have suggested that differentiation toward a differentiated osteoblast correlates with an increase in alkaline phosphatase activity 9) , bone related protein and ECM production 18,24) . Owen et al 23) reported that type 1 collagen, fibronectin, vitronectin and tenascin are among the components of the ECM produced by differentiated osteoblasts, and Postiglione et al 25) demonstrated that the ECM was easily produced, depending on the type of surface.…”
Section: Discussionmentioning
confidence: 99%